Usulan Perbaikan Mutu CPO dengan Metode Six Sigma pada PT. PSU PKS Tanjung Kasau - Dachi, Adi Syaputra; Syarif , Abdul Azis; Utama, Denny Walady (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. PSU Tanjung Kasau is one of the BUMD’s of North Sumatra Province in the agricultural sector. The product produced is Crude Palm Oil (CPO). CPO has quality parameters, namely free fatty acid (FFA) content, water content and dirt content. Based on data on the results of CPO production quality in January and February 2024, there are still several quality parameters that exceed the standards set by the company. Therefore, to determine the level of quality, factors that cause a decrease in the CPO level, and proposed improvements, research was carried out using the Six Sigma method with the stages of define, measure, analyze, improve and control (DMAIC). After processing, the CPO DPMO value was obtained of 676,451.85 with a sigma value of 1.04. Then using the Pareto diagram, it was obtained that the water content and free fatty acid content caused a decrease in CPO quality. Then based on the fishbone diagram, the human factor was obtained which was a lack of discipline, the material factor was bad qualityof TBS, and the machine factor was less than optimal machine performance and the method factor was not in accordance with the SOP. Proposed improvements to overcome the problems include conducting training and evaluation, increasing the supply of TBS and improving infrastructure, conducting regular monitoring and maintenance of machines, improving SOP’s and implementing SOP’s so that corporate governance can run well. Keywords : CPO, DMAIC, Quality, Six Sigma